THE SIGNIFICANT OF PROFESSIONAL INDEMNITY (PI) INSURANCE AMONG ENGINEERING CONSULTANCIES IN MALAYSIA - Wan Hussin, Wan Hasliyana; Ismail, Zulhabri (Journal of Technology Management and Business, 2016)
These days, society has becoming increasingly litigious, and this increases the chance for professionals to be brought in court against their negligence. Professional Indemnity (PI) Insurance is known to indemnify against negligence act. However, certain issues arise when its importance is questionable as well as its extent and impact could give towards professionalism is being doubted. A deeper understanding on the finer details of the cover available could assist engineers to choose PI Insurance as their risk transfer medium. This research aims to propose factors that will encourage engineering consultancies to insure for PI Insurance. In order to achieve the aim of the research, three objectives have been addressed, which are to determine the awareness and understanding of the PI Insurance among the engineering consultancies in the construction industry, to identify the benefits that will encourage engineering consultancies to secure their business with PI Insurance and to identify the factors that will encourage engineering consultancies to secure their business with PI Insurance. Acknowledging the fact that PI Insurance is relatively new to the Malaysian construction industry, the possibility of engineers to be exposed and aware with its importance could be low. A qualitative research was conducted through the semi-structured interview approach in answering to the curiosity. Eleven respondents from Perak and Selangor had participated in the process and through that, it is proven that the importance of PI Insurance was slightly understood by the engineers. This research had also indicated that insufficient amount of PI Insurance sum would not promise engineers’ business financial strength as it only covers up to certain amount, depending on the limit on indemnity. By insuring PI Insurance, it becomes an indicator that engineers will indemnify when negligence is present. Besides, it acts as marketing tool in terms of their integrity and capability that sets the business apart from others. In conclusion, factors to encourage engineers to insure for PI Insurance in Malaysian construction industry are proposed while considering its importance and its extent of usefulness to the engineers.